2014
DOI: 10.15713/ins.jcri.24
|View full text |Cite
|
Sign up to set email alerts
|

Anti-microbial activity of Punica granatum on streptococcus in dental caries patients and healthy individuals: A comparative study

Abstract: Background: Researchers today are driven toward the medicinal and therapeutic value of the natural products like Aloe vera, basil, turmeric, green tea, pomegranate (Punica granatum) to prevent dental caries. The aim of the present study was to determine the antimicrobial activity of pomegranate aril extract on streptococci in dental caries patients and healthy individuals. Materials and Methods:The study group included 40 subjects; age comprised of 18-26 years 20 dental caries patients were taken as an experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…When PPE is combined with hypochlorite and CHX, the antibacterial property must have enhanced. [21] Further in-vivo studies are required to confirm the results in a polymicrobial endodontic environment of root canal system.…”
Section: Discussionmentioning
confidence: 99%
“…When PPE is combined with hypochlorite and CHX, the antibacterial property must have enhanced. [21] Further in-vivo studies are required to confirm the results in a polymicrobial endodontic environment of root canal system.…”
Section: Discussionmentioning
confidence: 99%
“…Tannins could also inhibit important bacterial enzymes, such as glucosyltransferase which is important for binding of the bacteria to the tooth surface as well as to each other and if disrupted, it prevents the adherence mechanism of these organisms to tooth surface. 12 26 29 Another mechanism used by PG extract is the binding of phenolic compounds to carbohydrates and physiological metal ions, such as iron and copper making them unavailable for the microorganisms which affect the activity of metalloenzymes resulting in cell wall disruption. Polyphenols can also significantly affect the bacterial population by decreasing the pH of the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols can also significantly affect the bacterial population by decreasing the pH of the environment. 12 26 29 Although several studies have concluded that punicalagin is the major active constituent responsible for the antibacterial activity of PG, Lalwani et al stated that the synergistic effect of PG constituents is responsible for the anticariogenic effect of PG. 29 …”
Section: Discussionmentioning
confidence: 99%
“…It causes demineralization of inorganic tooth structure by metabolizing sucrose to lactic acid. It can also colonize tooth surfaces and initiate plaque formation through their ability to synthesize and bind extracellular polysaccharides (glucan) using the enzyme glucosyltransferase (Bai et al, 2016;Lalwani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Pomegranate (Punica granatum) is the predominant member of the Punicaceae family and one of the oldest fruits known in ancient Egypt. Pomegranate is a potent antioxidant with anti-carcinogenic and anti-inflammatory properties (Lalwani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%